Fibrous membrane prepared based on in-situ growth and application of fibrous membrane in toluene adsorption

The in-situ growth method on a fiber membrane enhances toluene adsorption capacity and recyclability by integrating UiO-66-NH2 crystals, addressing the limitations of conventional materials.

CN119221286AActive Publication Date: 2024-12-31JIANGNAN UNIV

Patent Information

Application Number
CN202411263766.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-31
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Conventional materials for toluene adsorption face issues such as low adsorption capacity, easy clogging, poor selectivity, and regeneration challenges, and MOF powder-based composites have reduced performance due to polymer wrapping the pore size, making recycling difficult.

Method used

A fiber membrane is prepared through in-situ growth by adding 2-aminoterephthalic acid and polyacrylonitrile to a solvent, electrospinning, thermal crosslinking, and then growing UiO-66-NH2 crystals on the fiber surface, enhancing adsorption performance and recyclability.

Benefits of technology

The fiber membrane achieves a high adsorption capacity of 188 mg/g with a specific surface area of 256 m²/g and maintains 97% adsorption capacity after five cycles, demonstrating effective toluene adsorption and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221286A_ABST
    Figure CN119221286A_ABST
Patent Text Reader

Abstract

The invention discloses a fibrous membrane prepared based on in-situ growth and application of the fibrous membrane in toluene adsorption, and belongs to the technical field of functional textiles. The method for preparing the fiber membrane based on in-situ growth comprises the following steps: (1) adding 2-aminoterephthalic acid and polyacrylonitrile into a solvent, and uniformly mixing to obtain a spinning solution; (2) performing electrostatic spinning on the spinning solution, and drying to obtain a fiber membrane; (3) placing the fiber membrane in an ethylene glycol solution, adding ethylenediamine, and carrying out thermal crosslinking; after the thermal crosslinking is finished, washing and drying to obtain a crosslinked fiber membrane; and (4) placing the cross-linked fiber membrane in a solvent, adding zirconium oxychloride, 2-aminoterephthalic acid and benzoic acid, and carrying out in-situ growth to obtain the fiber membrane prepared based on in-situ growth. The fiber membrane prepared on the basis of in-situ growth is high in methylbenzene adsorption capacity and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fiber membrane prepared based on in-situ growth and application in toluene adsorption, belonging to the technical field of functional textiles. Background Art

[0002] VOC (volatile organic compounds) are considered to be one of the most harmful pollutants to human health and ecosystems. Toluene, in particular, is a pollutant that urgently needs to be dealt with due to its high toxicity and wide range of sources (chemical production, paint production, house decoration, etc.). It is reported that exposure to toluene for more than 8 hours can have negative health effects and even pose a hidden risk of cancer in humans. In order to reduce the emission of benzene-based VOCs, several methods are available, including adsorption, catalytic oxidation and photocatalysis. Among them, the adsorption method is considered to be the most effective and economical technology for controlling VOC pollution due to its simple operation, high cost-effectiveness and low energy consumption.

[0003] Traditional materials for toluene adsorption include activated carbon, molecular sieves, diatomaceous earth, biochar and resins, which are widely used due to their simple preparation methods. However, these materials often face major limitations in their applications, such as low adsorption capacity, easy clogging, poor selectivity and regeneration challenges. In contrast, metal organic frameworks (MOFs) have significant advantages, with a surface area of ​​up to 10,000 m 2 / g, its porosity can reach 0.9cm 3 / g, which is much higher than traditional adsorption materials. At the same time, MOFs have the advantages of water stability, good chemical and thermal stability. They are widely used in: gas storage, catalysis, drug delivery and wastewater treatment. Among them, UiO-66 is different from other MOFs in that its structural unit is composed of [Zr6O4(OH)4] metal clusters coordinated and connected with 12 terephthalic acids (H2BDC), and has the highest coordination number of organic ligands and metal clusters. The Zr-O bond in UiO-66 has strong water stability; at the same time, it has many adsorption active sites. Moreover, UiO-66 is easy to modify. By modifying the functional groups, ideal physical and chemical properties can be obtained. By modifying the ligands with other functional groups and coordinating with Zr, functionalized Zr-MOFs such as UiO-66-NH2 and UiO-66-NO2 can be prepared. Although UiO-66 has many advantages as an adsorbent, most of them are obtained in powder form, which limits their use and recycling in large-scale applications such as gas adsorption.

[0004] At present, there are two main ways to combine MOF with nanofibers:

[0005] (1) Direct electrospinning, that is, adding the preformed MOF into the polymer spinning precursor solution, and directly obtaining the composite nanofiber membrane by electrospinning. This method is simple to operate and has few limitations, but MOF particles are easy to aggregate, resulting in blockage during spinning. In addition, since the diameter of MOF particles is smaller than that of the fiber, they are usually shielded inside the fiber and cannot function.

[0006] (2) In situ growth, i.e., the pure polymer fiber membrane obtained by spinning is immersed in a solution containing metal salts and organic ligands, and MOF is grown in situ on the fiber surface under high temperature and high pressure. This method greatly reduces the degree of MOF aggregation while increasing the MOF loading, and can improve the compatibility of MOF with polymer fibers. It is a more promising preparation method, but MOF is difficult to grow on the surface of ordinary polymers. It is usually necessary to embed MOF growth seeds in the fiber, such as adding metal salts or organic ligands to the spinning precursor solution to promote MOF growth. The difficulty of growing different MOF materials is also completely different.

[0007] At present, most studies are to prepare composite membranes by directly blending MOF powder with polymer matrix. However, in this process, the polymer will fully wrap and block the pore size of MOF, thereby reducing the adsorption performance, such as:

[0008] Patent CN 110496541 A discloses a modified composite fiber membrane for oil-water separation and a preparation method thereof; NH2-UiO-66(Zr) and PAN are blended and a super-hydrophobic, super-oleophilic nanofiber membrane with good oil-water separation properties is obtained by direct electrospinning; the composite fiber membrane has an adsorption capacity of 33.7 g / g for silicone oil, but no research has been conducted on the adsorption capacity of volatile organic compounds;

[0009] Patent CN 118416713 A discloses the preparation of a high-throughput, fast-adsorption PAN / PEI / UiO-66-NH2 adsorption membrane and its application in adsorbing Cr(VI); it uses direct electrospinning to wrap MOFs (UiO-66-NH2) in fibers, and uses a dynamic adsorption method to prepare a PAN / PEI / UiO-66-NH2 adsorption membrane at a pressure of 0.08MPa, while removing Cr(VI) at an industrial emission standard with a flux of 1150L*m -2 *h -1 , but the adsorption of volatile organic compounds has not been studied.

[0010] Moreover, the adsorption of metal ions, adsorption of grease and adsorption of gas are completely different; the adsorption of metal ions is through ion exchange; the adsorption of grease is through van der Waals force or π-π stacking; the adsorption of gas is intermolecular force, such as van der Waals force; that is: adsorbents for adsorbing metal ions, adsorbing grease and adsorbing gas are not universal.

[0011] Therefore, there is an urgent need to develop an adsorption material with a large toluene adsorption capacity, which can be recovered and recycled. Summary of the invention

[0012] [Technical issues]

[0013] Conventional materials for toluene adsorption have problems such as “low adsorption capacity, easy clogging, poor selectivity and regeneration challenges”;

[0014] Toluene adsorbed by MOF powder is difficult to recycle;

[0015] The composite film formed by MOF powder and polymer matrix has low adsorption performance for toluene.

[0016] [Technical solution]

[0017] In order to solve the above problems, the present invention provides a fiber membrane prepared based on in-situ growth, which can be used to adsorb toluene, has good adsorption effect and can be recycled.

[0018] The first object of the present invention is to provide a method for preparing a fiber membrane based on in-situ growth, comprising the following steps:

[0019] (1) adding 2-aminoterephthalic acid and polyacrylonitrile to a solvent and mixing them uniformly to obtain a spinning solution;

[0020] (2) electrospinning the spinning solution and drying it to obtain a fiber membrane;

[0021] (3) placing the fiber membrane in an alcohol solution, adding ethylenediamine, and performing thermal crosslinking; after the thermal crosslinking is completed, washing and drying to obtain a crosslinked fiber membrane;

[0022] (4) placing the cross-linked fiber membrane in a solvent, adding zirconium oxychloride, 2-aminoterephthalic acid and benzoic acid, and performing in-situ growth to obtain a fiber membrane prepared based on in-situ growth.

[0023] In one embodiment of the present invention, the solvent in step (1) is one or both of N,N-dimethylformamide and acetone.

[0024] In one embodiment of the present invention, the usage ratio of the solvent to polyacrylonitrile in step (1) is 8-12 mL: 1 g, more preferably 1 mL: 1 g.

[0025] In one embodiment of the present invention, the mass ratio of 2-aminoterephthalic acid to polyacrylonitrile in step (1) is 0.10-0.20:1, more preferably 0.15:1.

[0026] In one embodiment of the present invention, the temperature for uniform mixing in step (1) is 55-65°C, more preferably 60°C.

[0027] In one embodiment of the present invention, the parameters of electrospinning in step (2) are:

[0028] The voltage is 10-15 kV, the injection speed is 0.2-2 mL / h, the needle diameter is 0.2-1 mm, the receiving distance is 10-20 cm, the receiving roller speed is 60-240 rpm, the ambient temperature is 25-40° C., and the relative humidity is 15-60%.

[0029] In one embodiment of the present invention, the drying in step (2) is performed at 60-100° C. to volatilize the solvent.

[0030] In one embodiment of the present invention, the volume fraction of the alcohol solution in step (3) is 60-80%, more preferably 75%.

[0031] In one embodiment of the present invention, the alcohol solution in step (3) is an ethylene glycol solution or a propylene glycol solution, and the solvent is water.

[0032] In one embodiment of the present invention, the volume ratio of the alcohol solution to ethylenediamine in step (3) is 1 mL: 0.8-1.2 μL; more preferably 1 mL: 1 μL.

[0033] In one embodiment of the present invention, the usage ratio of the fiber membrane and the alcohol solution in step (3) is 100 mg: 80-120 mL.

[0034] In one embodiment of the present invention, the thermal crosslinking in step (3) is carried out at 130-140°C for 1-3 hours, more preferably at 135°C for 2 hours.

[0035] In one embodiment of the present invention, the washing in step (3) is performed using ethanol and water.

[0036] In one embodiment of the present invention, the drying in step (3) is carried out at 60-100°C.

[0037] In one embodiment of the present invention, the solvent in step (4) is one or both of N,N-dimethylformamide and acetone.

[0038] In one embodiment of the present invention, the ratio of the cross-linked fiber membrane to the solvent in step (4) is 100 mg: 80-120 mL.

[0039] In one embodiment of the present invention, the mass ratio of the cross-linked fiber membrane, zirconium oxychloride, 2-aminoterephthalic acid and benzoic acid in step (4) is 0.1:0.5-1.0:0.3-0.7:1-1.5; more preferably 0.1:0.75:0.5:1.25.

[0040] In one embodiment of the present invention, the in-situ growth in step (4) is carried out at 90-110° C. for 20-30 h.

[0041] The second object of the present invention is a fiber membrane prepared based on in-situ growth and obtained by the method described in the present invention.

[0042] In one embodiment of the present invention, the fiber membrane is a PAN nanofiber with a UiO-66-NH2 crystal structure loaded on the surface.

[0043] The third objective of the present invention is the application of the fiber membrane prepared based on in-situ growth in the field of environmental pollution.

[0044] The fourth object of the present invention is to provide a toluene adsorbent, which adopts the fiber membrane prepared based on in-situ growth described in the present invention.

[0045] The fifth object of the present invention is to provide a method for improving the toluene adsorption performance of MOF in polymer, which adopts the fiber membrane prepared based on in-situ growth according to the present invention.

[0046] The sixth object of the present invention is to provide a method for improving the toluene adsorption performance of polyacrylonitrile fiber membrane, which adopts the fiber membrane prepared based on in-situ growth described in the present invention.

[0047] [Beneficial Effects]

[0048] (1) The present invention loads the UiO-66-NH2 crystal structure on the surface of PAN nanofibers through electrospinning and in situ growth, so that it has good adsorption performance for toluene.

[0049] (2) The fiber membrane prepared based on in-situ growth described in the present invention has a high adsorption capacity for toluene and is recyclable and can be recycled.

[0050] (3) The specific surface area of ​​the fiber membrane prepared based on in-situ growth according to the present invention reaches 256 m 2 / g; the adsorption capacity for toluene reached 188mg / g, and the adsorption rate reached 4.3×10 -3 / min; and, after five adsorptions, the adsorption capacity for toluene only decreased by 3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the XRD pattern of the fiber membrane prepared based on in-situ growth in Example 1.

[0052] Figure 2 This is the infrared spectrum of the fiber membrane prepared based on in-situ growth in Example 1.

[0053] Figure 3 This is the SEM image of the fiber membrane prepared based on in-situ growth in Example 1.

[0054] Figure 4 This is the nitrogen adsorption-desorption curve of the fiber membrane prepared based on in-situ growth in Example 1.

[0055] Figure 5 This is the adsorption effect of the fiber membrane prepared based on in-situ growth in Example 1.

[0056] Figure 6 Comparison of the adsorption isotherms, adsorption kinetics (a), adsorption capacity (b) and velocity (c) of toluene for the fiber membranes prepared in Example 1 and Comparative Example 3.

[0057] Figure 7 This is the effect of different amounts of 2-aminoterephthalic acid on the properties of fiber membranes.

[0058] Figure 8 This is the SEM image of the fiber membrane obtained in Comparative Example 6.

[0059] Fig. 9 This is the SEM image of the fiber membrane obtained in Comparative Example 7.

[0060] Fig.10 This is the SEM image of the fiber membrane obtained in Comparative Example 12. DETAILED DESCRIPTION

[0061] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0062] Test method:

[0063] 1. Test of toluene adsorption performance (adsorption capacity, adsorption speed):

[0064] Preprocessing:

[0065] The samples were evenly placed in a quartz crucible. In a closed system, high-purity nitrogen (400 sccm) was used to purge the samples at 150°C for 180 min, with an average flow rate of 50 sccm to the samples.

[0066] test:

[0067] After the pretreatment, the sample environment was lowered to 25°C, wet nitrogen was used to bubble into toluene, and the nitrogen-carried toluene vapor (40 sccm in total) was proportioned with dry nitrogen (360 sccm), that is, the P / P0 of 25°C toluene was 0.1, and the gas was continuously blown to the sample surface for adsorption; after the adsorption equilibrium state was reached, the four-way valve switched the flow rate, and the wet flow rate + vapor flow rate (80 sccm in total) was re-proportioned with the dry flow rate (320 sccm) and then blown to the sample surface, and the adsorption process of 25°C toluene P / P0 was 0.2, until the adsorption equilibrium state was reached.

[0068] According to the above process, the flow ratios of dry and wet paths are adjusted in sequence so that the toluene P / P0 at 25°C is 0.3-0.4-0.5-0.6-0.7-0.8-0.9-0.8-0.8-0.6-0.5-0.4-0.3-0.2-0.1.

[0069] During the test, the samples at different analysis positions are continuously weighed using the high-resolution balance inside the instrument. The weighing data are processed by software and the buoyancy is calculated to obtain the adsorption amount-time curve. The saturated adsorption amount at each pressure point is then selected to obtain the isotherm.

[0070] 2. Test of toluene circulation performance:

[0071] Preprocessing:

[0072] The samples were evenly placed in a quartz crucible. In a closed system, high-purity nitrogen (400 sccm) was used to purge the samples at high temperature for 180 min at 150° C., with an average flow rate of 50 sccm to the samples.

[0073] test:

[0074] After the pretreatment, the sample environment was lowered to 25°C, and wet nitrogen was used to bubble into toluene. The nitrogen-carrying toluene vapor (320 sccm in total) was mixed with dry nitrogen (80 sccm), that is, the P / P0 of 25°C toluene was 0.8, and the gas was continuously blown to the sample surface to make it adsorb; after reaching the adsorption equilibrium state, the four-way valve switched the flow rate to high-purity nitrogen (400 sccm) and then blew it to the sample surface, and the desorption process of 25°C toluene P / P0 was 0, until the desorption equilibrium state was reached. Repeat the above process 5 times.

[0075] During the test, the samples at different analysis positions are continuously weighed using the high-resolution balance inside the instrument. The weighing value data is processed by software and the buoyancy is calculated to obtain the adsorption amount-time curve.

[0076] 3. Test of nitrogen adsorption and desorption curve:

[0077] 77K nitrogen adsorption and desorption test process:

[0078] Install the sample tube containing the sample on the instrument, add liquid nitrogen to the scale line in the liquid nitrogen cup, set the degassing plan and test plan, and click Start after the sample tube leak test passes to enter the fully automatic in-situ degassing test process;

[0079] (1) He gas test free space volume;

[0080] (2) In-situ vacuum heating degassing (pressure-controlled heating to prevent flying);

[0081] (3) Enter the adsorption-desorption test;

[0082] According to the P / P0 relative pressure point set in the test plan, it gradually changes from 0 to nearly 1 atmosphere, and the pressure change before and after the sample adsorption is measured by a high-precision pressure sensor, and then the adsorption or desorption amount of the gas is calculated according to the gas state equation; the adsorption amount-relative pressure curve is obtained, and the BET specific surface area and pore size distribution are calculated according to the nitrogen adsorption theoretical calculation formula. Raw materials used in the embodiment:

[0083] N,N-dimethylformamide: ≥97.5, AR;

[0084] 2-aminoterephthalic acid: AR;

[0085] Polyacrylonitrile: powder, average Mw = 150000, AR;

[0086] Ethylenediamine: AR;

[0087] Zirconium oxychloride: GR;

[0088] Benzoic acid: AR.

[0089] The solutions involved in the embodiments without specifying the solvent are water as the solvent, the % involved without specifying the meaning is mass percentage; the reactions involved without specifying the reaction temperature are room temperature reactions, and the room temperature is 20-30°C.

[0090] Example 1

[0091] A method for preparing a fiber membrane based on in-situ growth comprises the following steps:

[0092] (1) Add 0.15 g of 2-aminoterephthalic acid and 1 g of polyacrylonitrile to 10 mL of N,N-dimethylformamide, and stir and mix them at 60° C. to obtain a spinning solution;

[0093] (2) electrospinning the spinning solution at a voltage of 12 kV, a push injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30° C., and a relative humidity of 40%; drying the solution in a vacuum oven at 80° C. to volatilize the solvent in the fiber, and obtaining a fiber membrane (BP) containing 15% by mass of 2-aminoterephthalic acid;

[0094] (3) 100 mg of the fiber membrane was placed in 100 mL of 75% ethylene glycol solution, 100 μL of ethylenediamine was added, and thermal cross-linking was performed at 135°C for 2 h; after the thermal cross-linking was completed, it was washed with ethanol and deionized water for 3 times respectively, and dried in a vacuum oven at 80°C to obtain a cross-linked fiber membrane (ABP);

[0095] (4) 100 mg of the cross-linked fiber membrane was placed in 100 mL of N,N-dimethylformamide, and 0.75 g of zirconium oxychloride, 0.5 g of 2-aminoterephthalic acid, and 1.25 g of benzoic acid were added to carry out in situ growth in a reactor at 100 °C for 24 h to obtain a fiber membrane prepared based on in situ growth (UiO-66-NH2@ABP).

[0096] The fiber membrane prepared based on in-situ growth was tested for performance, and the test results are as follows:

[0097] (1) Surface structure characterization:

[0098] The XRD pattern of the fiber membrane prepared based on in-situ growth is shown in Figure 1 ,from Figure 1 It can be seen that characteristic peaks of 7.05° and 8.14° were observed in the fiber membrane, corresponding to the characteristic peaks of UiO-66-NH2, proving the synthesis of MOF.

[0099] The infrared spectrum of the fiber membrane prepared based on in situ growth is as follows Figure 2 .from Figure 2 It can be seen that at 620cm -1 and 770cm -1 The characteristic absorption peak at is related to the Zr-O bond, which means that UiO-66-NH2 is successfully synthesized on the fiber surface.

[0100] Combined, Figure 1 and Figure 2 It can be seen that UiO-66-NH2 does exist on the surface of the fiber membrane prepared in Example 1.

[0101] (2) Surface morphology characterization:

[0102] The SEM image of the fiber membrane prepared based on in situ growth is shown in Figure 3 .

[0103] The nitrogen adsorption-desorption curves of the fiber membrane prepared based on in situ growth are shown in Figure 2. Figure 4 .from Figure 4 It can be seen that the specific surface area of ​​the fiber membrane (UiO-66-NH2@ABP) prepared based on in situ growth is greatly improved, reaching 256m 2 / g.

[0104] (3) Characterization of adsorption performance:

[0105] The adsorption effect of fiber membrane prepared based on in situ growth is as follows Figure 5 ,from Figure 5 It can be seen that the adsorption capacity of the fiber membrane prepared based on in situ growth for toluene reaches 178 mg / g, and the adsorption rate reaches 4.3×10 -3 / min; and, after five adsorptions, the adsorption capacity for toluene only decreased by 3%.

[0106] Example 2

[0107] The amount of 2-aminoterephthalic acid in step (1) of Example 1 was adjusted to 0.10 g, and the other contents were kept the same as in Example 1 to obtain a fiber membrane prepared based on in-situ growth.

[0108] Example 3

[0109] The amount of 2-aminoterephthalic acid in step (1) of Example 1 was adjusted to 0.20 g, and the other contents were kept consistent with Example 1 to obtain a fiber membrane prepared based on in-situ growth.

[0110] Comparative Example 1

[0111] A method for preparing a fiber membrane based on direct spinning comprises the following steps:

[0112] (1) 0.75 g zirconium oxychloride, 0.5 g 2-aminoterephthalic acid, and 1.25 g benzoic acid were added to 10 mL N,N-dimethylformamide and reacted in a reactor at 100 °C for 24 h to synthesize a metal organic framework powder (MOF): UiO-66-NH2;

[0113] (2) Add 0.08 g of UiO-66-NH2 and 0.8 g of polyacrylonitrile powder to 10 mL of N,N-dimethylformamide and stir until the liquid is uniform to obtain a spinning solution;

[0114] (3) The spinning solution is subjected to electrospinning at a voltage of 12 kV, an injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30°C, and a relative humidity of 40%; the solution is placed in a vacuum oven at 80°C to dry and volatilize the solvent in the fiber, thereby obtaining a fiber membrane prepared based on direct spinning.

[0115] Comparative Example 2

[0116] A method for preparing a fiber membrane based on direct spinning comprises the following steps:

[0117] (1) 0.75 g zirconium oxychloride, 0.5 g 2-aminoterephthalic acid, and 1.25 g benzoic acid were added to 10 mL N,N-dimethylformamide and reacted in a reactor at 100 °C for 24 h to synthesize a metal organic framework powder (MOF): UiO-66-NH2;

[0118] (2) Add 0.24 g of UiO-66-NH2 and 0.8 g of polyacrylonitrile powder to 10 mL of N,N-dimethylformamide and stir until the liquid is uniform to obtain a spinning solution;

[0119] (3) The spinning solution is subjected to electrospinning at a voltage of 12 kV, an injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30°C, and a relative humidity of 40%; the solution is placed in a vacuum oven at 80°C to dry and volatilize the solvent in the fiber, thereby obtaining a fiber membrane prepared based on direct spinning.

[0120] Comparative Example 3

[0121] A method for preparing a fiber membrane based on direct spinning comprises the following steps:

[0122] (1) 0.75 g zirconium oxychloride, 0.5 g 2-aminoterephthalic acid, and 1.25 g benzoic acid were added to 10 mL N,N-dimethylformamide and reacted in a reactor at 100 °C for 24 h to synthesize a metal organic framework powder (MOF): UiO-66-NH2;

[0123] (2) Add 0.40 g of UiO-66-NH2 and 0.8 g of polyacrylonitrile powder to 10 mL of N,N-dimethylformamide and stir until the liquid is uniform to obtain a spinning solution;

[0124] (3) The spinning solution is subjected to electrospinning at a voltage of 12 kV, an injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30°C, and a relative humidity of 40%; the solution is placed in a vacuum oven at 80°C to dry and volatilize the solvent in the fiber, thereby obtaining a fiber membrane prepared based on direct spinning.

[0125] Comparative Example 4

[0126] The amount of 2-aminoterephthalic acid in step (1) of Example 1 was adjusted to 0.05 g, and the other contents were kept the same as in Example 1 to obtain a fiber membrane prepared based on in-situ growth.

[0127] The fiber membranes obtained in Example 1 and Comparative Examples 1-5 were subjected to performance tests, and the test results are as follows:

[0128] Figure 6 The adsorption isotherms, adsorption kinetics, and bar graphs of adsorption capacity and speed of toluene prepared by the fiber membranes of Example 1 and Comparative Example 3 are compared. Figure 6 It can be seen that the adsorption effect of the fiber membrane prepared by in situ growth is much higher than that of direct spinning.

[0129] Figure 7 The effect of different amounts of 2-aminoterephthalic acid on the properties of the fiber membrane. Figure 7 It can be seen that: at 0.05g, MOF grows too little and the adsorption performance is very low; at 0.2g, MOF grows too much, resulting in a decrease in the mechanical properties of the fiber (breaking strength of 1050kPa, elongation at break of 16%); at 0.15g, it has good adsorption performance; the MOF material on the fiber surface is relatively uniform and has good mechanical properties, with a breaking strength of 1200kPa and an elongation at break of 20%.

[0130] Table 1

[0131] example Adsorption capacity (mg / g) <![CDATA[Adsorption rate (10 -3 ×min -1 )]]> Example 1 178 4.3 Example 2 54 3.5 Example 3 166 3.9 Comparative Example 1 41 0.8 Comparative Example 2 77 1.3 Comparative Example 3 103 2.9 Comparative Example 4 19 1.9 <![CDATA[UiO-66-NH2 (powder)]]> 454 7.6

[0132] Comparative Example 6

[0133] The temperature of the in-situ growth in step (4) of Example 1 was adjusted to 80° C., and the other conditions were kept consistent with Example 1, thereby obtaining a fiber membrane prepared based on in-situ growth.

[0134] The SEM image of the obtained fiber membrane is shown in Figure 8 ,from Figure 8 It can be seen that there is too little MOF growth on the fiber and the adsorption performance is poor.

[0135] Comparative Example 7

[0136] The temperature of the in-situ growth in step (4) of Example 1 was adjusted to 120° C., and the other conditions were kept consistent with Example 1, to obtain a fiber membrane prepared based on in-situ growth.

[0137] The SEM image of the obtained fiber membrane is shown in Fig. 9 ,from Fig. 9 It can be seen that the amount of MOF growth on the fiber has increased, but it is uneven and the adsorption performance is poor.

[0138] Comparative Example 8

[0139] A method for preparing a fiber membrane based on in-situ growth comprises the following steps:

[0140] (1) adding 0.15 g of zirconium oxychloride and 1 g of polyacrylonitrile to 10 mL of N,N-dimethylformamide, stirring and mixing the mixture at 60° C. to obtain a spinning solution;

[0141] (2) The spinning solution was subjected to electrospinning at a voltage of 12 kV, a push injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30° C., and a relative humidity of 40%.

[0142] The results showed that adding zirconium oxychloride to the spinning solution did not allow for uniform spinning and thus failed to form a fiber membrane.

[0143] Comparative Example 9

[0144] The "0.5 g 2-aminoterephthalic acid" in step (4) of Example 1 was adjusted to "1.0 g 2-aminoterephthalic acid", and the rest was kept consistent with Example 1 to obtain a fiber membrane prepared based on in situ growth.

[0145] The results showed that excessive MOF growth occurred on the fiber, resulting in agglomeration and poor adsorption performance.

[0146] Comparative Example 10

[0147] The addition of "0.5 g of 2-aminoterephthalic acid" in step (4) of Example 1 was omitted, and the rest was kept consistent with Example 1 to obtain a fiber membrane prepared based on in-situ growth.

[0148] The results showed that there was too little MOF growth on the fiber and the adsorption performance was poor.

[0149] Example 4

[0150] A method for preparing a fiber membrane based on in-situ growth comprises the following steps:

[0151] (1) Add 0.15 g of 2-aminoterephthalic acid and 1 g of polyacrylonitrile to 10 mL of N,N-dimethylformamide, and stir and mix them at 60° C. to obtain a spinning solution;

[0152] (2) electrospinning the spinning solution at a voltage of 12 kV, a push injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30° C., and a relative humidity of 40%; drying the solution in a vacuum oven at 80° C. to volatilize the solvent in the fiber, and obtaining a fiber membrane (BP) containing 15% by mass of 2-aminoterephthalic acid;

[0153] (3) 100 mg of the fiber membrane was placed in 100 mL of 75% ethylene glycol solution, 100 μL of ethylenediamine was added, and thermal cross-linking was performed at 130°C for 3 h; after the thermal cross-linking was completed, it was washed with ethanol and deionized water for 3 times respectively, and dried in a vacuum oven at 80°C to obtain a cross-linked fiber membrane (ABP);

[0154] (4) 100 mg of the cross-linked fiber membrane was placed in 100 mL of N,N-dimethylformamide, and 0.6 g of zirconium oxychloride, 0.4 g of 2-aminoterephthalic acid, and 1.0 g of benzoic acid were added to carry out in situ growth in a reactor at 90 °C for 30 h to obtain a fiber membrane prepared based on in situ growth (UiO-66-NH2@ABP).

[0155] Example 5

[0156] A method for preparing a fiber membrane based on in-situ growth comprises the following steps:

[0157] (1) Add 0.15 g of 2-aminoterephthalic acid and 1 g of polyacrylonitrile to 10 mL of N,N-dimethylformamide, and stir and mix them at 60° C. to obtain a spinning solution;

[0158] (2) electrospinning the spinning solution at a voltage of 12 kV, a push injection speed of 1 mL / h, a needle diameter of 0.4 mm, a receiving distance of 15 cm, a receiving roller speed of 100 rpm, an ambient temperature of 30° C., and a relative humidity of 40%; drying the solution in a vacuum oven at 80° C. to volatilize the solvent in the fiber, and obtaining a fiber membrane (BP) containing 15% by mass of 2-aminoterephthalic acid;

[0159] (3) 100 mg of the fiber membrane was placed in 100 mL of 75% ethylene glycol solution, 100 μL of ethylenediamine was added, and thermal cross-linking was performed at 135°C for 2 h; after the thermal cross-linking was completed, it was washed with ethanol and deionized water for 3 times respectively, and dried in a vacuum oven at 80°C to obtain a cross-linked fiber membrane (ABP);

[0160] (4) 100 mg of the cross-linked fiber membrane was placed in 100 mL of N,N-dimethylformamide, and 0.9 g of zirconium oxychloride, 0.8 g of 2-aminoterephthalic acid, and 1.4 g of benzoic acid were added to carry out in situ growth in a reactor at 110 °C for 20 h to obtain a fiber membrane prepared based on in situ growth (UiO-66-NH2@ABP).

[0161] The fiber membranes obtained in Examples 4 and 5 were subjected to performance tests, and the test results are as follows:

[0162] Table 2

[0163] example Adsorption capacity (mg / g) <![CDATA[Adsorption rate (10 -3 ×min -1 )]]> Example 4 133 3.7 Example 5 154 3.9

[0164] Comparative Example 11

[0165] The literature (Li W, Wang W, Sun J, et al. Hydrophobic modification of UiO-66 by naphthyl ligand substitution for efficient toluene adsorption in a humiden environment [J]. Microporous and Mesoporous Materials, 2021, 326: 111357-. DOI: 10.1016 / j.micromeso.2021.111357.) discloses the use of naphthalene to replace UiO-66 to achieve toluene adsorption, but under the condition of zero humidity, its toluene adsorption amount is only 143 mg / g.

[0166] Comparative Example 12

[0167] The zirconium oxychloride in Example 1 was adjusted to zirconium tetrachloride, and the other aspects were kept consistent with Example 1 to obtain a fiber membrane prepared based on in-situ growth.

[0168] The results are as follows Fig.10 .from Fig.10 It can be seen that the crystal form of MOF synthesized by zirconium tetrachloride is not obvious and the generated MOF is not good.

[0169] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a fiber membrane based on in-situ growth, characterized in that: The steps include: (1) adding 2-aminoterephthalic acid and polyacrylonitrile to a solvent and mixing them uniformly to obtain a spinning solution; wherein the mass ratio of 2-aminoterephthalic acid to polyacrylonitrile is 0.10-0.20:1; (2) electrospinning the spinning solution and drying it to obtain a fiber membrane; (3) placing the fiber membrane in an alcohol solution, adding ethylenediamine, and performing thermal crosslinking; after the thermal crosslinking is completed, washing and drying to obtain a crosslinked fiber membrane; (4) placing the cross-linked fiber membrane in a solvent, adding zirconium oxychloride, 2-aminoterephthalic acid, and benzoic acid, and performing in-situ growth to obtain a fiber membrane prepared based on in-situ growth; wherein the in-situ growth is in-situ growth at 90-110° C. for 20-30 hours.

2. The method according to claim 1, characterized in that: In step (1), the ratio of solvent to polyacrylonitrile is 8-12 mL: 1 g.

3. The method according to claim 1, characterized in that The parameters of electrospinning in step (2) are: The voltage is 10-15 kV, the injection speed is 0.2-2 mL / h, the needle diameter is 0.2-1 mm, the receiving distance is 10-20 cm, the receiving roller speed is 60-240 rpm, the ambient temperature is 25-40° C., and the relative humidity is 15-60%.

4. The method according to claim 1, characterized in that: In step (3), the thermal crosslinking is carried out at 130-140° C. for 1-3 hours.

5. The method according to claim 1, characterized in that: In step (4), the mass ratio of the cross-linked fiber membrane, zirconium oxychloride, 2-aminoterephthalic acid and benzoic acid is 0.1:0.5-1.0:0.3-0.7:1-1.

5.

6. A fiber membrane prepared by in-situ growth according to the method described in any one of claims 1 to 5.

7. Application of the fiber membrane prepared based on in-situ growth as claimed in claim 6 in the field of environmental pollution.

8. A toluene adsorbent, characterized in that: The fiber membrane prepared based on in-situ growth as described in claim 6 is adopted.

9. A method for improving the toluene adsorption performance of MOF in polymer, characterized in that: The fiber membrane prepared based on in-situ growth as described in claim 6 is adopted.

10. A method for improving the toluene adsorption performance of polyacrylonitrile fiber membrane, characterized in that: The fiber membrane prepared based on in-situ growth as described in claim 6 is adopted.

Citation Information

Patent Citations

  • Method for preparing UiO-66-NH2 / UiO-66-SO3H functionalized composite PVDF nanofiber proton exchange membrane

    CN116779925A

  • Composite adsorbent based on MOF / polymer and preparation method thereof

    CN117548087A

  • Composite membrane for in-situ growth of metal organic framework in hollow nanofiber and preparation method of composite membrane

    CN118079669A

  • Iron-nickel MOF / polyacrylonitrile nanofiber membrane composite cathode, and preparation method therefor and use thereof

    WO2023231055A1

Cited By

  • Resistance type gas sensor based on PAN and UiO-66 compounding and preparation and application thereof

    CN121476316A

  • Defect MOF load-based TPU composite fiber membrane preparation method and application

    CN122875083A